Memórias sobre a ditadura militar no norte do Rio Grande do Sul: o destacamento volante da Brigada Militar (1964) - Adamczyk, Guilherme Luís (2018)
Between March 31 and April 1, 1964, the civil-military coup that took João Goulart out of the presidency of the Brazilian Republic was launched. Even in the first moments after the "revolution", so called by the conspirators, the government began what would be a recurring practice throughout the military regime: persecution, repression and torture. Bearing in mind the geographically and strategically important position of the state of Rio Grande do Sul, precisely because it was a frontier zone, the cradle of labor and where many groups of the eleven were found, one had great attention in relation to it. There were opponents of the military government in several parts of the country, not being excluded from this scenario the north of Rio Grande do Sul. Much is said that in smaller cities and in the interior of Brazil there was not so much repression, however, soon after the coup, to operate in Erechim Detachment Volante of the Military Brigade, making a kind of ideological patrol in the region, arresting and imposing mistreatment to the considered subversives. The indemnification processes consulted in the Public Archive of the State of Rio Grande do Sul allowed us to have access to the memory of ex-political prisoners, relatives or witnesses of the facts, it being possible, together with the crossing of studies of the historiography on the subject, to make an analysis of those events, and in this way we constructed a portraitnarrative of what was modus-operandi of the Detachment Steering wheel as responsible for identifying and repressing any suspicion of opposition to the coup The greatest concern of the police forces s at that time were the Groups of Eleven, and the action of the Military Brigade's Volunteer Detachment was always the same: arriving in the homes intimidating the residents, searching the whole house for weapons or material considered subversive, arresting the accused, and humiliating and sometimes assault the rest of the family. Following arrest, in police stations or prisons, interrogations were carried out on the basis of physical and psychological torture, in some cases for a few days, sometimes for weeks. After being released, these citizens should report weekly to the authorities and sign a sort of point book and continue to be monitored indefinitely.